2013
DOI: 10.1111/ejn.12333
|View full text |Cite
|
Sign up to set email alerts
|

Impaired slow axonal transport in diabetic peripheral nerve is independent of RAGE

Abstract: Diabetic peripheral nerve dysfunction is a common complication occurring in 30-50% of long-term diabetic patients. The pathogenesis of this dysfunction remains unclear but growing evidence suggests that it might be attributed, in part, to alteration in axonal transport. Our previous studies demonstrated that RAGE (Receptor for Advanced Glycation Endproducts) contributes to the pathogenesis of diabetic peripheral neuropathy and impairs nerve regeneration consequent to sciatic nerve crush, particularly in diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(69 citation statements)
references
References 43 publications
2
67
0
Order By: Relevance
“…The expression and modification of these cytoskeletal proteins (actin, neurofilament, tubulin) is believed to interfere with cytoskeletal assembly, and, thus, axonal transport [163]. RAGE is predicted to interactwith actin through its effector mDia1[124, 129, 157], but recent work has elegantly shown that slowed axonal transport in diabetic animals is independent of RAGE expression [129]. Despite the slowed transport of the RAGE/actin effector protein mDia1 in diabetic animals (wild type and RAGE knockout), RAGE itself was not differentially present between diabetic and control animals.…”
Section: Mechanisms Of Peripheral Neuropathymentioning
confidence: 99%
“…The expression and modification of these cytoskeletal proteins (actin, neurofilament, tubulin) is believed to interfere with cytoskeletal assembly, and, thus, axonal transport [163]. RAGE is predicted to interactwith actin through its effector mDia1[124, 129, 157], but recent work has elegantly shown that slowed axonal transport in diabetic animals is independent of RAGE expression [129]. Despite the slowed transport of the RAGE/actin effector protein mDia1 in diabetic animals (wild type and RAGE knockout), RAGE itself was not differentially present between diabetic and control animals.…”
Section: Mechanisms Of Peripheral Neuropathymentioning
confidence: 99%
“…Time-lapse experiments revealed that the average rate of neurofilament transport is that of fast axonal transport but it is delayed by continuous pauses for prolonged periods of time 30 ; this breakthrough observation laid ground for the current view of neurofilament transportation in the nervous system and provided insight into general mechanisms governing cytoskeletal protein cargo transportation. Even before that discovery, irrespective of the nature of neurofilament axonal transport, many authors noted that its impairment may contribute to the pathogenesis of neurodegenerative diseases such as: ALS [31][32][33][34] , Charcot-Marie-Tooth 19,38 . Impairment of neurofilament axonal transport might be caused by mutations/ change of function of transport proteins (indirect cause) or by changes in the neurofilament structure and/ or function (direct cause).…”
Section: Neurofilamentsmentioning
confidence: 99%
“…Another study, conducted in Alzheimer's model PS1/APP mice, revealed that the presence of phosphorylated tau protein affects molecular motors and the actin cytoskeleton, likely leading to alternations of axonal transport and abnormal metabolism of these proteins 58 . Observed impairment in actin axonal transport might be also contributed, as in case of neurofilament, to increased levels of glycation leading to subsequent changes in actin chemical structure that affect axonal transport 19,61 .…”
Section: Liprin αmentioning
confidence: 99%
See 2 more Smart Citations